Atomic and itinerant effects at the transition-metal x-ray absorption K pre-edge exemplified in the case of V 2O 3 - Hansmann, Philipp; Haverkort, Maurits W. (Physical review. B, Condensed matter and materials physics, 2012)
X-ray absorption spectroscopy is a well-established tool for obtaining information about orbital and spin degrees of freedom in transition-metal and rare-earth compounds. For this purpose usually the dipole transitions of the L (2p to 3d) and M (3d to 4f) edges are employed, whereas higher order transitions such as quadrupolar 1s to 3d in the K edge are rarely studied in that respect. This is due to the fact that usually such quadrupolar transitions are overshadowed by dipole-allowed 1s to 4p transitions and, hence, are visible only as minor features in the pre-edge region. Nonetheless, these features carry a lot of valuable information, similar to the dipole L-edge transition, which is not accessible in experiments under pressure due to the absorption of the diamond anvil pressure cell. We recently performed a theoretical and experimental analysis of such a situation for the metal-insulator transition of (V(1−x)Crx)2O3. Since the importance of the orbital degrees of freedom in this transition is widely accepted, a thorough understanding of quadrupole transitions of the vanadium K pre-edge provides crucial information about the underlying physics. Moreover, the lack of inversion symmetry at the vanadium site leads to on-site mixing of vanadium 3d and 4p states and related quantum mechanical interferences between dipole and quadrupole transitions. Here we present a theoretical analysis of experimental high-resolution x-ray absorption spectroscopy at the V K pre-edge measured in partial fluorescence yield mode for single crystals. We carried out density functional as well as configuration interaction calculations in order to capture effects coming from both itinerant and atomic limits.
Die Ziffern 2 und 3 im Titel sind tiefgestellt, der Buchstabe K wird im Text kursiv geschrieben
Gesehen am 02.11.2017